Outcomes with Tacrolimus-Based Immunosuppression After Kidney Transplantation from Standard- and Extended-Criteria Donors - A Post Hoc Analysis of the Prospective OSAKA Study - Albano, Laetitia; Banas, Bernard; Lehner, Frank; Glyda, Maciej; Viklicky, Ondrej; Schleibner, Stefan; Brown, Malcolm; Kamar, Nassim (Annals of transplantation, 2020)
BACKGROUND This post hoc analysis of data from the prospective OSAKA study evaluated the efficacy and safety of prolonged- and immediate-release tacrolimus in patients who received kidneys from extended-criteria (ECD) and standard-criteria (SCD) donors. MATERIAL AND METHODS Within the ECD and SCD groups, patients were randomized to one of 4 tacrolimus-based regimens (initial dose): Arm 1, immediate-release tacrolimus (0.2 mg/kg/day); Arm 2, prolonged-release tacrolimus (0.2 mg/kg/day); Arm 3, prolonged-release tacrolimus (0.3 mg/kg/day); Arm 4, prolonged-release tacrolimus (0.2 mg/kg/day) plus basiliximab. All patients received mycophenolate mofetil and bolus corticosteroids; Arms 1-3 also received tapered corticosteroids. ECDs met the definition: living/deceased donors aged ≥60 years, or 50-60 years with ≥1 other risk factor, and donation after circulatory death. Primary composite endpoint: graft loss, biopsy-confirmed acute rejection or renal dysfunction by Day 168. Outcomes were compared across treatment arms with the chi-squared or Fisher's exact test. RESULTS A total of 1198 patients were included in the analysis (ECD: n=620 [51.8%], SCD: n=578 [48.2%]). Patients with kidneys from ECDs were older versus SCDs (mean age, 55.7 vs. 44.5 years, p<0.0001). A higher proportion of patients with kidneys from ECDs versus SCDs met the primary composite endpoint (56.8% vs. 32.4%, p<0.0001). However, no statistically significant differences in clinical outcomes or the incidence of treatment-emergent adverse events were seen between treatment arms within each donor group. CONCLUSIONS Worse outcomes were experienced in patients who received kidneys from ECDs versus SCDs. Prolonged-release tacrolimus provided similar graft survival to the immediate-release formulation, with a manageable tolerability profile.
Keywords: Kidney Failure, Chronic; Humans; lidé středního věku; Delayed-Action Preparations; Drug Administration Schedule; Female; Aged; dospělí; přežívání štěpu; výsledek terapie; senioři; lidé; výběr dárců; imunosupresiva; imunosupresivní léčba; Adult; Immunosuppressive Agents; transplantace ledvin; ženské pohlaví; chronické selhání ledvin; Male; Middle Aged; Treatment Outcome; Donor Selection; Immunosuppression Therapy; léky s prodlouženým účinkem; Kidney Transplantation; Tacrolimus; takrolimus; mužské pohlaví; prospektivní studie; Graft Survival; rozvrh dávkování léků; Prospective Studies